The contributions of children's libraries in disadvantaged areas to critical thinking skills - Hakkoymaz, S (My University)
Critical thinking emerges as a crucial skill that can bring meaning to the lives of children, particularly those facing challenging living conditions. This qualitative study aims to examine the critical thinking tendencies of 30 children (15 girls and 15 boys) aged 7 to 10 from disadvantaged areas who experienced the 2023 Kahramanmaras, earthquake and regularly attended a children's library in Gaziantep, Turkey. The participants were selected using a purposive sampling method and participated consistently in workshops offered by the library. Data were collected through written interview forms designed to evaluate the children's critical thinking skills and assess the impact of the library programs. These data were analyzed using content analysis to gain a deeper understanding of the children's thought processes and the influence of library programs on these processes. The findings revealed that the library environment and workshop activities significantly enhanced the children's critical thinking skills. Through group discussions and interactions with diverse information sources in the library, children developed key components of critical thinking, including the ability to evaluate different perspectives, analyze information, and think independently. This study highlights the pivotal role of children's libraries in supporting critical thinking skills, particularly among children in disadvantaged areas. Based on the study's findings, it is recommended to diversify and expand workshop programs in children's libraries that target critical thinking skills. Additionally, implementing community-based educational programs in collaboration with local communities could further strengthen children's critical thinking abilities, equipping them to become more capable individuals in the future.
Keywords: Critical thinking; Children's libraries; Disadvantaged children in earthquake area